Mitochondrial apoptotic pathway mediated the Zn-induced lipolysis in yellow catfish Peteobagrus fulvidraco. (October 2018) - Li, Dan-Dan; Luo, Zhi; Ling, Shi-Cheng; Wu, Kun; Chen, Guang-Hui; Cheng, Jie
Abstract: In the study, effects of waterborne zinc (Zn) exposure on apoptosis were investigated, and the potential mechanism of apoptosis participating in the Zn-induced variations of lipid metabolism was explored in a low vertebrate, yellow catfish Pelteobagrus fulvidraco . We found that Zn induced occurrence of apoptosis of livers and hepatocytes in yellow catfish. Waterborne Zn also increased hepatic transcriptional levels of p53, cytochrome c (Cycs), caspase 3a (Casp3a) and caspase 3b (Casp3b) of yellow catfish. Zn increased caspase 3 activity and reduced the mitochondrial permeability transition (MTP) in yellow catfish hepatocytes. Z-VAD-fmk (caspase inhibitor) and CsA pretreatment (MTP inhibitor) attenuated the Zn-induced apoptosis and reduction in MTP. Z-VAD-fmk pretreatments attenuated the Zn-induced increase in transcriptional levels of p53, Cycs and Casp3b although the differences were not statistically significant between the Zn group and Zn + Z-VAD-fmk group. In contrast, Zn and N-acetylcysteine (NAC) did not significantly influence the reactive oxygen species (ROS) production. Zn significantly reduced triglyceride (TG) content, increased the activities of carnitine palmitoyltransferase 1 (CPT I), hormone-sensitive lipase (HSL) and adipose TAG lipase (ATGL), and the transcriptional levels of p53, Cycs and caspase 3b of the hepatocytes; these Zn-induced effects on TG contents, activities of CPT I, HSL and ATGL, and mRNA levels of p53, Cycs and caspase 3b could partly be reversed by Z-VAD-fmk, suggesting that Zn induced the mitochondrial-mediated apoptosis and reduced lipid accumulation. Taken together, our study demonstrated the importance of mitochondria-mediated apoptosis in Zn-induced lipolysis, which suggested a new mechanism for elucidating metal element influencing lipid metabolism. Highlights: Zn exposure induced the occurrence of apoptosis in the livers and hepatocytes of yellow catfish. Zn-induced apoptosis was mediated by intrinsic mitochondrial pathways. Zn-induced mitochondrial apoptotic pathways were related to mitochondrial permeability transition. Zn induced the mitochondrial-mediated apoptosis and resulted in hepatic lipolysis. Our study elucidates the importance of mitochondria-mediated apoptosis in Zn-induced lipolysis.